(untitled) (Studia austriaca, 2016)
This essay investigates the literary work of Sebastian Brunner (1814-1893), a politically conservative Austrian writer. Focusing on his satirical novel «Die Prinzenschule zu Möpselglück» (1848), it argues two theses. First, it will show that the religiously and politically conservative worldview the novel articulates is not a regression behind Enlightenment ideals. Second, it argues that this novel, despite its strong polemic against the political agenda of the Jungdeutschen, is a direct heir to their aesthetic innovations of the genre.